Martian surface microtexture from orbital CRISM multi-angular observations: A new perspective for the characterization of the geological processes. (1st September 2016) - Fernando, J.; Schmidt, F.; Douté, S.
Abstract: The surface of Mars has a high morphological and mineralogical diversity due to the intricacy of external, internal processes, and exchanges with the atmosphere, the hydrosphere and the cryosphere. In particular, liquid water played an important role in surface evolution. However, the origin, duration and intensity of those wet events have been highly debated, especially in the clay-bearing geological units. Similarly, questions still remain about magma crystallization and volatile quantity of the dominant basaltic crust. In this work, six sites having hydrated minerals, salts and basaltic signatures (i.e., Mawrth Vallis, Holden crater, Eberswalde crater, Capri mensa, Eridania basin, Terra Sirenum) are investigated in order to better characterize the geological processes responsible for their formation and evolution (e.g., fluvial, lacustrine, in situ weathering, evaporitic, volcanic and aeolian processes). For that purpose, we use orbital multi-angular measurements from the Compact Reconnaissance Imaging Spectrometer for Mars (CRISM) instrument on-board the Mars Reconnaissance Orbiter spacecraft to analyze the manner in which light is scattered by the surface materials (photometry) in the near-infrared range (at 750 nm). The surface bidirectional reflectance depends on the composition but also on the surface microtexture such as the grain size distribution, morphology, internal structure and surface roughness, tracers of the geological processes. The Hapke semi-analytical model of radiative transfer in granular medium is used to model the surface bidirectional reflectance estimated at 750 nm from the orbital measurements after an atmospheric correction. The model depends on different radiative properties (e.g., single scattering albedo, grain phase function and regolith roughness) related to the surface composition and microtexture. In particular previous laboratory works showed that the particle phase function parameters, which describe the characteristics of the volume scattering, are sensitive to the grain morphology and internal structure. The surface material photometric parameters estimated from the CRISM multi-angular observations at 750 nm are compared to the geological units in order to better characterize the geological processes. The photometric results show a high diversity of surface scattering behaviors (from a broad and backward scattering behavior to a narrow and forward scattering behavior) that suggests a high diversity of surface microtexture. A narrow forward scattering behavior has been detected for the first time from martian orbital data and observed in peculiar regions dominated by salt-bearing and clay-bearing materials. Hence the martian photometric results suggest that Mars experimented varied geological processes still preserved in the material microtexture. This study also demonstrates that these properties provide complementary information to mineralogy and geomorphology to better constrain the geological processes. Abstract : Highlights: The surface microtexture is estimated at grain scale from orbit using photometry. A high diversity of microtexture suggests that Mars has a complex geological history. A narrow forward scattering behavior has been detected in salt and clay materials. Photometry provides complementary information to mineralogy and geomorphology. Mars experimented varied geological processes still preserved in the microtexture.